2022
DOI: 10.1029/2022gl098925
|View full text |Cite
|
Sign up to set email alerts
|

The Color of Earth’s Lakes

Abstract: Although water color is a fundamental property of freshwater ecosystems, the global distribution of lake color remains unknown. Here, we used 5.14 million color records derived from satellite images during 2013–2020 to determine the modal water color of 85,360 representative lakes worldwide. We find that globally, lake modal colors span the visible spectrum with a bimodal distribution of blue versus non‐blue (green‐brown), with 31% of lakes being blue and 69% being non‐blue. Both climate and lake morphology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…However, Yang et al. (2022) found that increasing summer temperatures in the future would induce more green and brown lakes. Our analysis showed the contribution of air temperature to the shifts did not cause differences in raising or reducing λd ${\lambda }_{d}$ (Figures 3b and 3c), suggesting that the bluing lakes possibly resulted from multiple factors rather than only temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Yang et al. (2022) found that increasing summer temperatures in the future would induce more green and brown lakes. Our analysis showed the contribution of air temperature to the shifts did not cause differences in raising or reducing λd ${\lambda }_{d}$ (Figures 3b and 3c), suggesting that the bluing lakes possibly resulted from multiple factors rather than only temperature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oligotrophic lakes were usually blue, eutrophic lakes greener, and eutrophic lakes with high suspended sediment were usually brown. It should be noted that λd ${\lambda }_{d}$ has limited information in determining constituent concentrations compared to hyperspectral measurements, though it has been used to reveal patterns and trends in water color (Gardner et al., 2021; Giardino et al., 2019; Topp et al., 2021; Yang et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the browning increases water color and can reduce light availability, the increased input of allochthonous matter also provides nutrients, which can promote phytoplankton biomass and thus help to compensate for the light limitation (Corman et al 2018). As brown lakes are projected to become more common in the future (Yang et al 2022), it will be useful to understand the effect of browning on the light availability to phytoplankton.…”
mentioning
confidence: 99%